Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1017/s0022112089001230
|View full text |Cite
|
Sign up to set email alerts
|

A natural low-frequency oscillation of the flow over an airfoil near stalling conditions

Abstract: An unusually low-frequency oscillation in the flow over an airfoil is studied experimentally as well as computationally. Wind-tunnel measurements are carried out with two-dimensional airfoil models in the chord Reynolds number (Rc) range of 0.15 × 105−3.0 × 105. During deep stall, at α [gsim ] 18°, the usual ‘bluff-body shedding’ occurs at a Strouhal number, Sts ≈ 0.2. But at the onset of static stall around α = 15°, a low-frequency periodic oscillation is observed, the corresponding Sts being an order of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
96
2

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(118 citation statements)
references
References 22 publications
20
96
2
Order By: Relevance
“…On the other hand, the absence of an explanation for the low-frequency flapping in the present laminar flow reconstruction is in line with the conclusión of Zaman et al [32] and Yon and Katz [31], who related it to turbulent shear-layers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the absence of an explanation for the low-frequency flapping in the present laminar flow reconstruction is in line with the conclusión of Zaman et al [32] and Yon and Katz [31], who related it to turbulent shear-layers.…”
Section: Discussionsupporting
confidence: 90%
“…In their experimental measurements Yon and Katz identified different frequencies on the pressure signal, one related to the wake instability (St ~ 0.15) and another with high amplitude and low frequency St ~ 0.04. Both Yon and Katz [31] and Zaman et al [32] concluded independently that the low frequency fluctuations are related to a violent motion of the leading edge shear-layer, termed shear-layer flapping, resulting from a transitional or turbulent state of the separated shear-layer. Here, the oscillatory behaviour of the flow could be explained in the context of a modal linear instability analysis with the inclusión of the other less-amplified but still unstable oscillatory modes that were recovered in the BiGlobal instability analysis (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this low-frequency behavior is very sensitive to three-dimensional effects and turbulence, which could be a reason why it may not be observed in experiments. There is, however, evidence of similar behavior in literature, but this was reported for airfoils near stall conditions [11].…”
Section: A Naca0018supporting
confidence: 62%
“…Two regions of increased fluctuation can be identified, the first extending along the displacement thickness, upstream ofx h . In this region, small variations in the shear layer distance from the wall due to the flapping mechanism (Zaman et al 1989) result in substantial changes in the value of u. Flapping does not affect the wall-normal velocity to the same extent, thus this region is absent in the σ v field. In contrast, the second region of elevated fluctuations is evident in both standard deviation fields downstream ofx h .…”
Section: Statistical Featuresmentioning
confidence: 94%
“…Marxen & Henningson (2011) argued that, if irregular disturbances are present in the incoming flow, such as freestream turbulence in free flight or wind-tunnel experiments, the aforementioned feedback loop may explain the occurrence of an intermittent shear layer fluctuation associated with LSBs, often referred to as "flapping" (e.g. Zaman et al 1989). Adding to this argumentation, significant reduction of the flapping behaviour due to artificial monochromatic forcing has been noted by Dovgal & Boiko (1994) and Sandham (2008), related to the locking of the bubble dynamics to modes of constant amplitude.…”
Section: Introductionmentioning
confidence: 99%